Congenital Heart Disease: An Immunological Perspective - Singampalli, Kavya L.; Jui, Elysa; Shani, Kevin; Ning, Yao; Connell, Jennifer P.; Birla, Ravi K.; Bollyky, Paul L.; Caldarone, Christopher A.; Keswani, Sundeep G.; Grande-Allen, Kathryn Jane (Frontiers in Cardiovascular Medicine, 2021)
Congenital heart disease (CHD) poses a significant global health and economic burden - despite advances in treating CHD reducing the mortality risk, globally CHD accounts for approximately 300,000 deaths yearly. Children with CHD experience both acute and chronic cardiac complications, and though treatment options have improved, some remain extremely invasive. A challenge in addressing these morbidity and mortality risks is that little is known regarding the cause of many CHDs and current evidence suggests a multifactorial etiology. Some studies implicate an immune contribution to CHD development; however, the role of the immune system is not well understood. Defining the role of the immune and inflammatory responses in CHD therefore holds promise in elucidating mechanisms underlying these disorders and improving upon current diagnostic and treatment options. In this review, we address the current knowledge coinciding CHDs with immune and inflammatory associations, emphasizing conditions where this understanding would provide clinical benefit and challenges in studying these mechanisms.